2007
DOI: 10.1074/jbc.m705672200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the SspA Serine Protease Zymogen of Staphylococcus aureus Proceeds through Unique Variations of a Trypsinogen-like Mechanism and Is Dependent on Both Autocatalytic and Metalloprotease-specific Processing

Abstract: The serine and cysteine proteases SspA and SspB of Staphylococcus aureus are secreted as inactive zymogens, zSspA and zSspB. Mature SspA is a trypsin-like glutamyl endopeptidase and is required to activate zSspB. Although a metalloprotease Aureolysin (Aur) is in turn thought to contribute to activation of zSspA, a specific role has not been demonstrated. We found that pre-zSspA is processed by signal peptidase at ANA 29 Binding of glutamate within the active site of zSspA is energetically unfavorable, but gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 50 publications
4
65
0
Order By: Relevance
“…In several instances, this processing leads to enzyme activation, for instance, in the case of the S. aureus extracellular proteases themselves. These proteins are secreted as inactive zymogens and cleaved by signal peptidase to release them from the membrane, and subsequent additional processing steps at defined sites finally lead to the full activation of these enzymes (33). Through previous work, it has been established that the S. aureus LTA synthase enzyme LtaS is efficiently processed at a defined site during bacterial growth (32,35,46).…”
Section: Discussionmentioning
confidence: 99%
“…In several instances, this processing leads to enzyme activation, for instance, in the case of the S. aureus extracellular proteases themselves. These proteins are secreted as inactive zymogens and cleaved by signal peptidase to release them from the membrane, and subsequent additional processing steps at defined sites finally lead to the full activation of these enzymes (33). Through previous work, it has been established that the S. aureus LTA synthase enzyme LtaS is efficiently processed at a defined site during bacterial growth (32,35,46).…”
Section: Discussionmentioning
confidence: 99%
“…However, aureolysin seems to act in synergy with other factors from the bacterial supernatant to degrade C3 fully. Because previous studies indicated that aureolysin is required for activation of the V8 protease (53), this suggests that the V8 protease may act as a cofactor for aureolysin-mediated FIGURE 8. Aureolysin is required and sufficient for cleavage of C3 by S. aureus supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory profragment of V8 protease is 39 residues long and is removed in a multistep process (29,30). The newly formed N terminus becomes directly a part of the S1 specificity pocket contrary to the N terminus of chymotrypsin, which only influences the folding of the polypeptide chain constituting the S1 pocket.…”
Section: Protease Zymogens Assure Protection Against Unwantedmentioning
confidence: 99%